The understanding of male and female students on the basic concepts of evolution - Lud Waluyo; Abdulkadir Rahardjanto (University of Muhammadiyah Malang, 2022)
Students' understanding of the concepts that underlie evolution are often less than optimal and make it difficult for them to accept the theory of evolution. The aimed of this study were to: 1) map students' knowledge of Mutation and Recombination (M and R); and 2) analyze the effect of gender on their chairperson. This survey research involving 42 Biology Education students at the University of Muhammadiyah Malang was conducted in April 2021. An online questionnaire containing 34 items related to six aspects of M and R was used as an instrument for data announcements. The results, only 30.95% in the category of good knowledge. The aspect of knowledge related to the causes of M and R has the highest average accuracy of answers, while the aspect of the difference between M and R is the lowest. Only three aspects were significantly correlated with each other. Furthermore, gender has no significant effect on all aspects of student knowledge. The low knowledge of students reported in this study needs to be followed up by improving the quality of Genetics lectures to strengthen students' basic understanding of evolution.